Hearing loss and tinnitus: association with employment and income among young adults - Jacobs, Molly; Tobener, Elizabeth N.; Ellis, Charles (Frontiers in Audiology and Otology, 2025)
IntroductionAuditory difficulties (i.e., hearing loss, tinnitus, both) are correlated with unemployment, underemployment, and reduced income, particularly among minority populations, Although hearing loss is more common among Non-Hispanic White individuals, receipt of otologic and hearing healthcare is far less common among Non-Hispanic Black individuals with hearing loss and tinnitus. The objective of this study was to evaluate differences in employment and income among young adults with hearing loss, tinnitus, and both.MethodsData from Waves IV (2008) (N = 15,701) and V (2016–18) (N = 11,955) of the National Longitudinal Study of Adolescent to Adult Health (ADD Health) contained self-reported hearing loss for individuals aged 24–43. Logistic and ordinal dependent variable regression evaluated the likelihood of having paid employment and the level of income, respectively, between categories of hearing loss controlling for sample heterogeneity. Findings were validated using a two-part model with racial/ethnic interactions.ResultsAmong respondents, 5.81%−8.87% reported tinnitus only, 0.82%−1.39% reported hearing loss only, and 0.54%−1.41% reported both. Regression analysis showed that Black individuals were less likely to have paid employment (OR = 0.72, CI = 0.58, 0.90) and earned lower income (OR = 0.85, CI = 0.82, 0.88) than White individuals. There were no differences in the likelihood of employment/income between those with tinnitus/both conditions and those with no difficulties, but those with hearing loss had lower likelihood of paid employment (OR = 0.88, CI = 0.85, 0.87) and income (OR = 0.95, CI = 0.94, 0.97). Black and Hispanic individuals with hearing loss were less likely to have paid employment (Black individuals OR = 0.02, CI = 0.00, 0.18; Hispanic individuals OR = 0.01, CI = 0.00, 0.15). Black individuals with hearing loss (OR = 0.79, CI = 0.64, 0.95), tinnitus (OR = 0.83, CI = 0.80, 0.88), and other respondents with both (OR = 0.72, CI = 0.68, 0.77) earned lower income.ConclusionResults suggest that hearing loss is associated with a reduced likelihood of employment and employment advancement particularly among young Black and Hispanic individuals.